ANALISIS PERAN LCT TERHADAP VOLUME DAN NILAI EKSPOR-IMPOR INDONESIA DALAM HUBUNGAN PERDAGANGAN DENGAN MALAYSIA, THAILAND, DAN JEPANG - Hatta, Hatta (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
The pandemic, followed by the war in Ukraine, has caused inflation rates to soar. Such conditions almost certainly trigger a response in the form of tight monetary policies. When implemented by developed countries, these policies may lead to capital outflows from developing countries. To counter this, similar monetary measures are often adopted by the latter. This monetary phenomenon keeps recurring. Capital outflows are just one of many factors contributing to high foreign exchange volatility, which adversely impacts the economy and trade. Consequently, many have begun exploring ways to reduce dependency on foreign currencies by adopting the Local Currency Transaction (LCT) scheme.This study aims to examine the relationship or correlation between LCT and the value and volume of Indonesia’s exports and imports with its three trading partners: Malaysia, Thailand, and Japan. Using a non-parametric quantitative research method complemented by the Spearman test (as well as the Wilcoxon test to validate result consistency), it was found that the relationship between LCT and the value and volume of exports and imports predominantly (11 out of 12 analysis categories) exhibits a negative correlation. This indicates that LCT tends to reduce trade value or volume. Future efforts could include enhancing outreach or even providing training for business actors on the positive benefits of LCT, particularly targeting sectors that have yet to optimally utilize LCT. A preliminary step is understanding business actors’ perceptions, preferences, and challenges regarding the use of LCT. Additionally, comparisons should be made with practices similar to the LCT scheme, such as the SML scheme implemented in MERCOSUR countries and the ACU in South and Central Asian nations.